Ability to write job application letter by class x11 students of smk negeri 1 hilimegai construction and property business department Academic year 2023/2024 - Samabahagia Laia (Journal of Education Innovation and Curriculum Development, 2023)
The purpose of this research is to describe the use of spelling in job application letters. The benefit of this research is to increase knowledge and insight and provide an overview of learning to write job application letters. The subfocus in this research is the ability to use spelling (capital letters, period punctuation and comma punctuation). The research method used in this research is a descriptive method and a qualitative form, namely analyzing letters and explaining errors in the form of words. The data source in this research is class XII students at SMK Negeri 1 Hilimegai. The data in this research are job application letters made by class XII students of SMK Negeri 1 Hilimegai. The technique used in this research is a measurement technique which aims to determine the level of students' ability to write job application letters. The results of this research are that there are still errors in the use of systematics, namely in the letter address, letter content and closing greeting. Based on the analysis, there are still many errors in making effective sentences. Spelling errors in job application letters include the use of capital letters, full stops and commas.